2003
DOI: 10.1161/01.cir.0000058704.45646.0d
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-Hydrogen Exchange Inhibition During Ventricular Fibrillation

Abstract: Background-Inhibition of the sarcolemmal sodium-hydrogen exchanger isoform-1 (NHE-1) is emerging as a promising novel strategy for ameliorating myocardial injury associated with ischemia and reperfusion. We investigated whether NHE-1 inhibition (with cariporide) could minimize mechanical and electrical myocardial abnormalities that develop during ventricular fibrillation (VF) and improve outcome using a porcine model of closed-chest resuscitation. Methods and Results-Two groups of 8 pigs each were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(34 citation statements)
references
References 31 publications
(31 reference statements)
3
29
0
Order By: Relevance
“…Its effect on myocardial carbon dioxide concentration is not clear. Be that as it may, elegant studies of cardiac arrest induced by ventricular fibrillation revealed improvement in cardiac function during fibrillation [25] and significant attenuation of postresuscitation ventricular arrhythmias including prevention of recurrent episodes of ventricular fibrillation with cariporide and other NHE1 inhibitors in both pig and rat models (table 1) [26,27,28,29,30,31,32]. …”
Section: Cardiac Arrestmentioning
confidence: 99%
“…Its effect on myocardial carbon dioxide concentration is not clear. Be that as it may, elegant studies of cardiac arrest induced by ventricular fibrillation revealed improvement in cardiac function during fibrillation [25] and significant attenuation of postresuscitation ventricular arrhythmias including prevention of recurrent episodes of ventricular fibrillation with cariporide and other NHE1 inhibitors in both pig and rat models (table 1) [26,27,28,29,30,31,32]. …”
Section: Cardiac Arrestmentioning
confidence: 99%
“…41,42 A functionally similar phenomenon known as ischemic contracture was reported in the early seventies during open heart surgery when operations were conducted under normothermic conditions in fibrillating hearts 43,44 and more recently after prolonged intervals of untreated VF. 45 However, ischemic contracture is associated with profound reductions in myocardial ATP and often leads to a “stony heart” heralding irreversible ischemic injury.…”
Section: Myocardial Abnormalities During Cardiac Resuscitationmentioning
confidence: 65%
“…Experimentally, these repolarization abnormalities are short-lived (5 to 10 minutes) and coincide with the interval of increased propensity for ventricular arrhythmias and recurrent VF. 42 These repolarization abnormalities and reperfusion arrhythmias can be markedly attenuated by NHE-1 inhibition. 42 …”
Section: Myocardial Abnormalities During Cardiac Resuscitationmentioning
confidence: 99%
See 2 more Smart Citations